Full inhibition of Whangkeumbae pear polyphenol oxidase enzymatic browning reaction by l-cysteine. (15th November 2018) - Zhou, Xiran; Xiao, Yanju; Meng, Xianghong; Liu, Bingjie
Highlights: Polyphenol oxidase (PPO) of Whangkeumbae pear was extracted and purified. PPO enzymatic browning reaction was inhibited by l -cysteine completely. The inhibitory type was of non-competitive inhibition. Specific activity of PPO was 519, 895.73 U/mg protein, the molecular mass was 44 kDa. Abstract: The enzymatic browning reaction caused by polyphenol oxidase (PPO) has a negative effect on the processing of fruits and vegetables. However, some chemical inhibitors have been used to prevent enzymatic browning reaction, although they may be toxic and potentially hazardous to use in food. In this study, PPO was isolated and purified from the Whangkeumbae pear, and four food grade inhibitors were used to prevent the enzymatic browning reaction. The results showed that the PPO activity increased by 32.93-fold; its yield was 0.2 U/100 U, and the specific activity was 519, 895.73 U/mg protein. The molecular weight of the PPO was approximately 44 kDa. The most potent inhibitor was l -cysteine, which fully inhibited the PPO activity at a concentration of 0.8 mg/mL. The type of inhibition of l -cysteine was noncompetitive. It suggests that l -cysteine can be utilized to prevent enzymatic browning reaction during the processing of pear juice.